PCM cooling of mobile devices - Shepherdson Tabitha Maria. (2011)
The ever-evolving landscape of technology has led to an influx of mobile gadgets catered to the discerning consumer. Tablet computers need to offer better processing capabilities whilst decreasing in size. Shrinking devices emphasizes the need for proper cooling methods to prevent overheating and damaging internal components.